Are we drinking our neurones away?. Issue 6571 (28th February 1987) - Harper, C; Kril, J; Daly, J
Abstract : A quantitative neuropathological necropsy study of the human cerebral cortex showed that the number of cortical neurones in the superior frontal cortex in chronic alcoholic patients is significantly reduced compared with that in controls matched for age and sex. The number of neurones in the motor cortex did not differ significantly between the controls and alcoholics, but in both cortical regions there was evidence that alcoholic patients had smaller (shrunken) neurones than controls. Further studies are necessary to identify other regions of the cerebral cortex that are selectively damaged in brain damage associated with alcohol.